Political Skill in Organizations - Ferris, Gerald R.; Treadway, Darren C.; Perrewé, Pamela L.; Brouer, Robyn L.; Douglas, Ceasar; Lux, Sean (Journal of Management, 2007)
Political skill is a construct that was introduced more than two decades ago as a necessary competency to possess to be effective in organizations. Unfortunately, despite appeals by organizational scientists to further develop this construct, it lay dormant until very recently. The present article defines and characterizes the construct domain of political skill and embeds it in a cognition—affect—behavior, multilevel, meta-theoretical framework that proposes how political skill operates to exercise effects on both self and others in organizations. Implications of this conceptualization are discussed, as are directions for future research and practical implications.